Art Therapy sebagai Strategi Intervensi Depresi pada Remaja: Suatu Model Terapeutik - Fadillah Khairunnisah; Resti Azani Tania; Ati Kusmawati (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
Depression in adolescents is a significant mental health issue in Indonesia, with its prevalence increasing every year. Adolescence is a transitional period marked by complex physical, social, and psychological changes. During this phase, adolescents often face emotional instability, academic pressure, social demands, and confusion in establishing self-identity. These factors can trigger prolonged stress and increase the risk of depression. Appropriate prevention and intervention efforts are crucial to address this issue. One approach that has proven effective is art-based group therapy. Art therapy provides a space for adolescents to express their thoughts and feelings creatively through visual media, which can help them understand themselves, manage their emotions, and build social skills. This study used the Systematic Literature Review method to identify, analyze, and synthesize the results of studies related to the effectiveness of art therapy on adolescent mental health. Data sources were obtained from various national and international journals relevant to the keywords "Art Therapy", "adolescent depression", and "mental health". The results of the literature review indicate that art therapy consistently has positive impacts, including reducing depressive symptoms, increasing self-confidence, strengthening interpersonal skills, and developing emotional intelligence. The creative process in this therapy encourages adolescents to be more open, able to process emotional experiences, and find positive ways to deal with problems. Based on these findings, Art Therapy is recommended for ongoing implementation in schools and communities as part of mental health programs. This intervention serves not only as a means of recovery but also as a preventative measure in building adolescents' psychological resilience, enabling them to grow and develop optimally amidst the challenges of modern life.